Exergames as an Effective Alternative to Real Environmental Tennis Training for Adolescents - Fábio Flôres; André Silva; Renata Willig; Ana Reyes; Joana Serpa; Priscila Marconcin; Fernando Vieira; Denise Soares; Nuno Casanova (MDPI AG, 2024)
(1) Background: The popularity of motion-sensing computer-based games, like virtual reality (VR) exergames, is increasing among adolescents. However, their efficacy compared to conventional physical training methods remains unclear. This study investigated whether VR exergames produce effects on reaction time (RT) comparable to traditional tennis training in school-aged adolescents. (2) Methods: In total, 130 adolescents (mean age: 15.6 ± 2.0 years; 67 boys: 15.5 ± 2.2 years; 63 girls: 15.7 ± 1.8 years) were recruited in schools and assigned to one of three groups: VR exergame (G1, n = 39), tennis training (G2, n = 25), or control (G3, n = 66). Participants' RTs were evaluated before and after the interventions. G1 engaged in VR exergames for 8 min, G2 underwent traditional tennis training for 30 min, and G3 did not participate in any physical activity. (3) Results: Our results indicated that in G3, girls exhibited slower RTs compared to boys (p < 0.0). No differences were observed in RTs when comparing G1 and G2. (4) Conclusions: Sex appeared to influence RT, with girls showing slower RTs than boys in G3. The findings suggest that VR exergames and traditional tennis training have similar impacts on RT. This indicates the potential of VR exergames as an alternative to conventional physical training for improving RT in adolescents.